Phylogeny of Plant CAMTAs and Role of AtCAMTAs in Nonhost Resistance to Xanthomonas oryzae pv. oryzae - Rahman, Hafizur; Yang, Juan; Xu, You-Ping; Munyampundu, Jean-Pierre; Cai, Xin-Zhong (Frontiers in Plant Science, 2016)
Calmodulin-binding transcription activator (CAMTA) constitutes one of the most important Ca2+/CaM-regulated transcription factor families in plants. Nevertheless, the phylogeny, protein interaction network and role in nonhost resistance of plant CAMTAs are not well understood. In this study, 200 CAMTA genes were identified from 35 species representing four major plant lineages. The CAMTA genes were conserved in multicellular land plants but absent in unicellular eukaryotes, and were likely to emerge from the fusion of two separate genes encoding a CAMTA-like protein and an IQ/CaM binding motif containing protein, respectively, in the embryophyta lineage ancestor. Approximately one fourth of plant CAMTAs did not contain a TIG domain. This non-TIG class of CAMTAs seems to have newly evolved through mutation of some key amino acids in the TIG domain of flowering land plants after divergence from the non-flowering plants. Phylogenetic analysis classified CAMTA proteins into three major groups and nine distinct subgroups, a result supported by protein domain and motif conservation analyses. Most (59.0% and 21.5%) of the identified CAMTA genes contained 12 or 11 introns, respectively. Gene duplication, intron invasion, enlargement and turnover, as well as exon rearrangements and skipping have apparently occurred during evolution of the CAMTA family. Moreover, 38 potential interactors of six Arabidopsis CAMTAs were predicted and 10 predicted target genes of AtCAMTA3 exhibited changes in expression between Atcamta3 mutants and wild-type plants. The majority of predicted interactors are transcription factors and/or Ca2+/CaM-regulated proteins, suggesting that transcriptional regulation of the target genes might be the dominant functional mechanism of AtCAMTAs, and AtCAMTAs might act together with other Ca2+ signaling components to regulate Ca2+-related biological processes. Furthermore, functional analyses employing Atcamta mutants revealed that AtCAMTA3 negatively regulated the immunity triggered by flg22 and nonhost resistance to Xanthomonas oryzae pv. oryzae via repressing accumulation of reactive oxygen species probably by targeting CBP60G, EDS1 and NDR1 and involving SA pathway.